Irrigation frequency at final cycle of hardwood seedling production - Oro, Priscilla; Dranski, João Alexandre Lopes; Malavasi, Ubirajara Contro; Malavasi, Marlene de Matos (Revista de Ciências Agroveterinárias, 2016)
This study aimed to quantify the effects of irrigation frequency at the end of the cultivation of Enterolobium contortisiliquum and Peltophorum dubium seedlings. The study followed a completely randomized design with six irrigation frequencies of five replications of ten seedlings. Daily irrigation for 15 days was followed by irrigation every 3 days for 15 days in seedlings of both species and resulted in the reduction of height growth, altered partitioning of below and above ground dry biomass, high integrity of cell membranes from root tissue, and increased seedling survival under water stress. Quantification of cell membrane integrity from root tissue through conductivity showed good prediction of seedling survival.